طريقة التعلم التعاوني وأثرها على تحصيل مادة الرياضيات لدى تلاميذ السنة الرابعة متوسط - ديدي، اللاحقة; قاسمي، صفية (جامعة الوادي university of Eloued, 2017)
تهدف هذه الدراسة إلى الكشف عن أثر استراتيجية التعلم التعاوني على تحصيل مادة الرياضيات لدى تلاميذ السنة الرابعة من التعليم المتوسط. وانطلقت الدراسة من التساؤل الرئيسي: ما أثر طريقة التعلم التعاوني على تحصيل التلاميذ في مادة الرياضيات؟ كما بحثت الدراسة في الفروق بين درجات المجموعتين الضابطة والتجريبية في اختبار تحصيلي أُعد خصيصًا لهذه الدراسة، إضافة إلى الفروق حسب متغير الجنس (ذكور / إناث). وللتحقق من الفرضيات، تم اعتماد المنهج شبه التجريبي، حيث أُجريت الدراسة على عينة قصدية مكونة من 40 تلميذًا وتلميذة. وتم تحليل البيانات باستخدام المتوسط الحسابي، والانحراف المعياري، واختبار "ت" (T-test). وأسفرت النتائج عن ما يلي: وجود تأثير إيجابي لاستراتيجية التعلم التعاوني على تحصيل مادة الرياضيات. وجود فروق ذات دلالة إحصائية بين متوسط درجات المجموعة التجريبية والمجموعة الضابطة لصالح التجريبية. عدم وجود فروق ذات دلالة إحصائية في نتائج المجموعة التجريبية بين الذكور والإناث. This study aims to investigate the impact of the cooperative learning strategy on mathematics achievement among fourth-year middle school students. The research was guided by the main question: What is the effect of cooperative learning on students' performance in mathematics? The study also explored differences between the control and experimental groups in a specially designed achievement test, as well as differences based on gender (male/female). To test the hypotheses, the quasi-experimental method was adopted, and the study was conducted on a purposive sample of 40 students. Data were analyzed using arithmetic means, standard deviation, and the T-test. The findings were as follows: Cooperative learning had a positive impact on students’ achievement in mathematics. There were statistically significant differences between the experimental and control groups in favor of the experimental group. No statistically significant differences were found between males and females in the experimental group
دراسة ميدانية في متوسطة الشهيد حمة لخضر
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: التعلم التعاوني; التحصيل الدراسي; الرياضيات; Cooperative Learning; Academic Achievement; MATHEMATICS